Diversity in finance: An overview - Reinhard H. Schmidt (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
This paper aspires to provide an overview of the issue of diversity of banking and financial systems and its development over time from a positive and a normative perspective. In other word: how different are banks within a given country and how much do banking systems and entire financial systems differ between countries and regions, and do in-country diversity and between-country diversity change over time, as one would be inclined to expect as a consequence of globalization and increasingly global standards of regulation? As the first part of this paper shows, the general answer to these questions is that there is still today a surprisingly high level of diversity in finance. This raises the two questions addressed in the second part of the paper: How can the persistence of diversity be explained, and how can it be assessed? In contrast to prevailing views, the author argues that persistent diversity should be regarded as valuable in a context in which there is no clear answer to the question of which structures of banking and financial systems are optimal from an economic perspective. – – Der Beitrag behandelt die Diversität von Bank- und Finanzsystemen in Deutschland, der Europäischen Union und weltweit und deren Veränderungen im Zeitablauf und damit zugleich die Frage, ob sich die Bank- und Finanzsysteme im Zeitablauf an einander angleichen. Allgemein wird vermutet, dass unter dem Einfluss der Globalisierung und der zunehmend international werdenden Regulierung Unterschiede immer mehr verschwinden und dass dies wirtschaftspolitisch wünschenswert ist. Der im ersten Teil des Beitrags zusammengefasste empirische Befund ist allerdings, dass das Ausmaß der Diversität in den letzten Jahren erstaunlich wenige abgenommen hat. Dies wirft die zwei Fragen auf, denen der zweite Teil des Beitrags gewidmet ist: Wie ist es zu erklären, dass sich eine höhere Diversität erhalten hat, als weithin vermutet wird, und wie ist Diversität im Finanzsektor zu bewerten? Wie der Verfasser argumentiert, ist angesichts der Tatsache, dass man nicht weiß und nicht wissen kann, welche Strukturen im Finanzsektor optimal sind, Diversität ökonomisch als vorteilhaft und damit als erhaltenswert einzustufen.
urn:nbn:de:hebis:30:3-507370
Keywords: 330; diversity; finance; banking systems; financial systems